Pure Money for a Sound Economy - Sandra Schmidt (University of Heidelberg, Department of Economics, 2015)
At present, the world-economy is exceedingly fragile. Debt levels of nations peak. Monetary assets increase, too, and concentrate in the hands of few. In this paper, I show that a mechanism at the root of today's monetary system entails an inherently fragile economy. I simulate the consequences of this mechanism within a macroeconomic model. I motivate a new monetary system that gives money the role it should have: to facilitate complex interactions in a stable environment.
urn:nbn:de:bsz:16-heidok-181158
Keywords: 330; Money; debt; banks and inequality Reform of the monetary system; equity-based money; Internationale Wirtschaft; Währungssystem